Preserved muscle oxidative metabolic phenotype in newly diagnosed non‐small cell lung cancer cachexia. Issue 2 (15th April 2015) - Op den Kamp, Celine M.; Gosker, Harry R.; Lagarde, Suzanne; Tan, Daniel Y.; Snepvangers, Frank J.; Dingemans, Anne‐Marie C.; Langen, Ramon C.J.; Schols, Annemie M.W.J.
Abstract: Background: Cachexia augments cancer‐related mortality and has devastating effects on quality of life. Pre‐clinical studies indicate that systemic inflammation‐induced loss of muscle oxidative phenotype (OXPHEN) stimulates cancer‐induced muscle wasting. The aim of the current proof of concept study is to validate the presence of muscle OXPHEN loss in newly diagnosed patients with lung cancer, especially in those with cachexia. Methods: Quadriceps muscle biopsies of comprehensively phenotyped pre‐cachectic ( n  = 10) and cachectic ( n  = 16) patients with non‐small cell lung cancer prior to treatment were compared with healthy age‐matched controls ( n  = 22). OXPHEN was determined by assessing muscle fibre type distribution (immunohistochemistry), enzyme activity (spectrophotometry), and protein expression levels of mitochondrial complexes (western blot) as well as transcript levels of (regulatory) oxidative genes (quantitative real‐time PCR). Additionally, muscle fibre cross‐sectional area (immunohistochemistry) and systemic inflammation (multiplex analysis) were assessed. Results: Muscle fibre cross‐sectional area was smaller, and plasma levels of interleukin 6 were significantly higher in cachectic patients compared with non‐cachectic patients and healthy controls. No differences in muscle fibre type distribution or oxidative and glycolytic enzyme activities were observed between the groups. Mitochondrial protein expression and gene expression levels of their regulators were also not different. Conclusion: Muscle OXPHEN is preserved in newly diagnosed non‐small cell lung cancer and therefore not a primary trigger of cachexia in these patients.